Association between long-term exposure to fine particulate matter and diabetic retinopathy among diabetic patients: A national cross-sectional study in China. (September 2021) - Shan, Anqi; Chen, Xi; Yang, Xueli; Yao, Baoqun; Liang, Fengchao; Yang, Ze; Liu, Fangchao; Chen, Song; Yan, Xiaochang; Huang, Jianfeng; Bo, Shaoye; Tang, Nai-Jun; et al.
Highlights: This is a national-wide study conducted across the rural Chinese population. The OR of PM2.5 for diabetic retinopathy was 1.41 (1.27, 1.57). The effect of PM2.5 was stronger in participants with alcohol consumption. A satellite-based spatiotemporal model was used to estimate PM2.5 levels. Abstract: Background: While the relationship between ambient air pollution and diabetes mellitus has recently been reported, data on the association between fine particulate matter (PM2.5 ) and diabetic complications are limited, especially in microvascular diseases such as diabetic retinopathy. Objectives: To investigate the associations between long-term exposure to PM2.5 and the prevalence of diabetic retinopathy in adult diabetic patients in rural China. Methods: The study population was based on the Rural Epidemiology for Glaucoma in China (REG-China), a national cross-sectional survey conducted in rural China. This analysis selected diabetic patients with or without diabetic retinopathy. A satellite-based spatiotemporal model was used to estimate personal PM2.5 exposure. Logistic regression models were used to investigate the effect of long-term PM2.5 exposure on diabetic retinopathy. Results: The analysis included 3111 diabetic participants, 329 of whom were diagnosed with diabetic retinopathy. The median level of exposure to PM2.5 from 2000 to2016 was 59.9 μg/m 3 . For each 10 μg/m 3 increase in PM2.5, the adjusted odds ratio (95% confidence interval) for diabetic retinopathy was 1.41 (1.27, 1.57). In subgroup analyses, the effect of PM2.5 on diabetic retinopathy was significantly stronger in participants who self-reported alcohol consumption. Conclusion: These findings suggest that long-term exposure to high PM2.5 was associated with the risk of diabetic retinopathy among diabetic patients in rural China.